2006
DOI: 10.1002/anie.200600321
|View full text |Cite
|
Sign up to set email alerts
|

Soft Synthesis of Single‐Crystal Silicon Monolayer Sheets

Abstract: Transparent Si nanosheets with a thickness of 0.37 nm are produced by chemically exfoliating calcium disilicide with propylamine hydrochloride (PA⋅HCl; see picture, Ca white, Si red). The nanosheets have a two‐dimensional silicon backbone and are an order of magnitude thinner than previously reported silicon nanostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
140
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 238 publications
(145 citation statements)
references
References 16 publications
3
140
2
Order By: Relevance
“…To achieve this, Mg-doped CaSi 2 was used as a starting material to decrease the strength of the interactions between the Ca 2+ and (Si ¹ ) n layers. 36) The immersion of bulk CaSi 1.85 Mg 0.15 in a solution of propylamine hydrochloride led to the deintercalation of the calcium ions, which was accompanied by the evolution of hydrogen. The CaSi 1.85 Mg 0.15 was then converted into a mixture of SiNSs and an insoluble black metallic solid.…”
Section: Synthesis Of Nanosheetsmentioning
confidence: 99%
“…To achieve this, Mg-doped CaSi 2 was used as a starting material to decrease the strength of the interactions between the Ca 2+ and (Si ¹ ) n layers. 36) The immersion of bulk CaSi 1.85 Mg 0.15 in a solution of propylamine hydrochloride led to the deintercalation of the calcium ions, which was accompanied by the evolution of hydrogen. The CaSi 1.85 Mg 0.15 was then converted into a mixture of SiNSs and an insoluble black metallic solid.…”
Section: Synthesis Of Nanosheetsmentioning
confidence: 99%
“…It is noted here that several challenges, such as controlling the Ca content in Ca x Si 2 and chemically exfoliating silicene layers from CaSi 2 , have been in progress. [ 21 ] In summary, we reported the results of ARPES study on tr3-CaSi 2 which is regarded as Ca-intercalated multilayer silicene. In the ARPES-derived band structure, we observed the massless Dirac-cone π-electron dispersions at the K(H) point in the Brillouin zone, together with the σ-band dispersions at the Γ point.…”
Section: Communicationmentioning
confidence: 98%
“…[ 21 ] Mixture of 99.999 wt% Si and 99.99 wt% Ca with the Ca-excess off-stoichiometric composition Ca 1.1 Si 2 was used as a starting material, since Ca is likely to evaporate from the CaSi 2 melt due to the high vapor pressure. This starting material was melted in a Ta crucible by high-frequency induction heating under an argon atmosphere, and cooled down to the room temperature to obtain a polycrystalline CaSi 2 ingot.…”
mentioning
confidence: 99%
“…One atomic thick crystalline form of the silicon atoms with sp 3 bond arranged in a honeycomb lattice structure so called Silicene ( fig. 1a), has been experimentally observed by Nakano, et al for the first time [11]. First principles calculation based on density functional theory (DFT) showed that despite carbon atoms that make two demensional planar sheet, Silicene makes stable bounds in the semi two dementional (semi-2D) hexagon form [12].…”
Section: Introductionmentioning
confidence: 93%